Indicadores de saúde bucal e qualidade de vida - Henriques, Cristiane [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
O objetivo deste estudo foi avaliar a autopercepção e as condições de saúde bucal de pacientes maiores de 50 anos, residentes em Araraquara-SP, verificando o grau de reprodutibilidade dos indicadores empregados.O planejamento estatístico incluiu estimativa de prevalência, por ponto e por intervalo de 95% de confiança (IC95%), estimativa de concordância pela estatística kappa e testes de associação com nível de significância de 5%. Inicialmente, foi verificado, entre idosos, nível ruim de autopercepção, com associação não-significativa com doença periodontal (p=0,5133), cárie radicular (p=0,9636) e uso de prótese (p=0,3286). Posteriormente, entre 149 pacientes maiores de 50 anos, atendidos na FOAr- UNESP e no Centro Regional de Reabilitação de Saúde de Araraquara-SP, determinou-se a prevalência das principais doenças bucais. Observou-se que aproximadamente 61% (IC95%: 53% 69%) dos indivíduos apresentaram lesão de cárie radicular e cerca de 69% (IC95%: 62% 76%) doença periodontal. Adicionalmente, considerando-se os sextantes, o sextante definido pelos números dos dentes 33-43, obteve maior prevalência de doença periodontal (60,3%) e 22% dos pacientes apresentaram o sextante definido pelos números dos dentes 13-23 desdentado. Para avaliação da autopercepção utilizou-se o Geriatric Oral Health Assessment Index (GOHAI). A maioria dos entrevistados afirmou nunca ter sofrido limitações (físicas, psicológicas, dor ou desconforto) devido a seus dentes ou próteses. Observou-se que 71,8% relataram sempre estarem felizes com o aspecto de seus dentes ou prótese e 77,9% afirmaram sempre se preocupar ou ter cuidados com seus dentes, gengivas ou próteses. Entretanto, 25,7% apresentaram freqüentemente problemas mordendo ou mastigando alimentos como carne sólida ou maçã e para 30,9% dos indivíduos houve sensibilidade nos dentes ou gengivas ao contato com calor,...

The objective of this study was to evaluate the self perceived and the conditions of oral health of patients in aged 50 years and over, living in Araraquara-SP, checking the rate of reproducibility of indicators used.The statistic planning included prevalence rates by point and by 95% confidence interval had been calculated (CI 95%), estimation of agreement by kappa statistic and tests of association with significance level of 5%. Initially, it was found among the elderly, poor level of self perceived, with non-significant association with periodontal disease (p = 0.5133), root caries (p = 0.9636) and use of prosthesis (p = 0.3286). Later, between 149 patients older than 50 years, treatment in the Araraquara Dental School and in the Regional Center of Health of Araraquara- SP, were determinated the prevalence of the main oral diseases. Approximately 61% (CI95%: 53% 69%) of the individuals had presented lesion of root caries and about 69% (CI95%: 62% 76%) periodontal disease. Additionally, considering the sextants, the sextant defined for the numbers of teeth 33-43, presented the highest prevalence of periodontal disease (60.3%) and 22% of the pacients had the sextant defined for the numbers of teeth 13-23 toothless.In order to evaluate the perceived oral health, it was used the Geriatric Oral Health Assessment Index (GOHAI). The majority of the interviewed patients had no limitations (physical, psychological, pain or discomfort) caused by their teeth, gums or prosthesis. Additionally, 71.8% always were pleased or happy with the looks of their teeth, gums or prosthesis and 77.9% were always worried or concerned about the problems with their teeth, gums or prosthesis. However, 25.7% had trouble biting or chewing any kind of food, such as firm meat or apples and for 30.9% of the individuals had their teeth or gums sensitive to hot, cold or sweets...(Complete abstract click electronic access below)
Keywords: Saúde bucal; Cárie radicular; Doenças periodontais; Odontologia geriátrica; Qualidade de vida; Oral health; Root caries; Periodontal diseases; Geriatric dentistry; Quality of life